Cowden Syndrome Diagnosed by Bilateral Breast Cancer with Lhermitte-Duclos Disease: A Case Report - Morisaki, Tamami (Case Rep Oncol, 2020)
Cowden syndrome is extremely rare and is characterized by multiple hamartomas in various tissues, including the skin, mucous membranes, gastrointestinal tract, breast, thyroid, and brain, and has an increased risk of breast, thyroid, and uterine cancers. Here, we report a case of Cowden syndrome diagnosed following presentation with bilateral breast cancer and provide a discussion of the relevant literature. A 47-year-old woman with a tumor in her right breast was referred to our hospital. She was diagnosed with bilateral breast cancer upon imaging and underwent a bilateral mastectomy and sentinel lymph node biopsy. Previously, she had undergone total thyroidectomy to treat a thyroid tumor. Approximately 3 years later, she was diagnosed with Lhermitte-Duclos disease affecting her left cerebellar hemisphere. As her sister and mother had also been diagnosed with breast cancer, we suspected that she might have an inherited disease. Since 80% of individuals with Cowden syndrome have a mutation in the phosphatase and tension homolog (PTEN) gene, we did not perform any genetic testing. Instead, we used the syndrome's pathognomonic criteria and major criteria (breast cancer, thyroid tumor, and Lhermitte-Duclos disease) to diagnose our patient with Cowden syndrome. While treatment of Cowden syndrome is currently limited to strategies that can manage the symptoms, patients are at an increased risk of certain cancers and require regular screening to allow for early detection of disease.